Preparation and Investigation of High Surface Area Aerogels from Crosslinked Polypropylenes - Coufal, Radek; Fijalkowski, Mateusz; Adach, Kinga; Bu, Huaitian; Karl, Christian W; Mikysková, Eliška; Petrík, Stanislav (Polymers, 2024)
Polypropylene-based aerogels with high surface area have been developed for the first time. By chemical crosslinking of polypropylene with oligomeric capped-end amino compounds, followed by dissolution, thermally induced phase separation, and the supercritical CO2 drying process or freeze-drying method, the aerogels exhibit high specific surface areas up to 200 m2/g. Moreover, the silica-cage multi-amino compound was utilized in a similar vein for forming hybrid polypropylene aerogels. According to the SEM, the developed polypropylene-based aerogels exhibit highly porous morphology with micro-nanoscale structural features that can be controlled by processing conditions. Our simple and inexpensive synthetic strategy results in a low-cost, chemically resistant, and highly porous material that can be tailored according to end-use applications.
Keywords: polypropylene; supercritical drying; thermally induced phase separation; crosslinking; aerogel; freeze-drying